Semi-Active Scissors-Seat Suspension With Magneto-Rheological Damper - Zhu, Hongtao; Rui, Xiaoting; Yang, Fufeng; Zhu, Wei; Gu, Junjie (Frontiers in Materials, 2020)
A cab seat suspension with magneto-rheological (MR) fluid damper is introduced in this paper. A unified-format model for MR damper is proposed to describe the dynamic characteristics of MR damper. Also, A simple force-inverse model and a viscous damping tracking model are used for coil current solution. Digital integrator and Extended Kalman Filter are respectively adopt to obtain the vibration velocity of chair frame and the relative motion velocity of MR damper piston. New skyhook control base on viscous damping tracking is apply to semi-active seat suspension. In the simulation, compared with passive seat suspension under different displacement excitation (2Hz-sine, 4Hz-sine, 6Hz-sine, 8Hz-sine and random), the acceleration RMS (root mean square) of the seat suspension with MR damper is reduced by 52.2%, 32.2%, 41.3%, 50.8% and 34.6% respectively,; In the experiment, the acceleration RMS is reduced by 11.2%, 41.2%, 45.8% and 31.5% respectively under different displacement excitation (2Hz-sine, 4Hz-sine, 6Hz-sine and 8Hz-sine).